On-Site Investigation and Diagnosis of Hazardous Street Section in Erbil Street Network - Abdulhakim Othman Salih kozapanky (Zanco Journal of Pure and Applied Sciences, 2025)
Accidents place a significant burden on the national economy due to their potential to cause disability, death, health issues, property damage, social distress, and environmental harm. The current study seeks to investigate an accident prone location in Erbil Street Network "in Kurdistan region- Iraq" and implement the procedures outlined in the Highway Safety Improvement Program (HSIP). The process involves characterizing the accidents, diagnosing the issues, and assessing field conditions to identify the contributing factors. Based on this, countermeasures are suggested to significantly improve safety. Factor analysis was employed to determine and rank the most influential factors contributing to the accidents. By addressing these significant factors with targeted measures, future accidents can be reduced. Data analysis was conducted focusing on micro-level factors such as traffic characteristics, road user behavior, collision types, road and geometric features, street furniture, and environmental conditions. The study involved characterizing accidents, diagnosing field conditions, identifying contributory factors, and recommending countermeasures to substantially enhance safety. Through the analysis of the collected accident data, it is shown that run over (pedestrian accidents) is the dominant type and happened at morning and afternoon peak hours. It contribute to vehicles speed which generally exceeded the average speed for the link. The output of the diagnosis phase is a set of applicable countermeasures for the accident prone location and the degree of confidence in each countermeasure.This research will assist transportation designers in understanding accident causes and implementing appropriate measures during road construction planning and for existing conditions. It provides a framework for reducing accidents both in the short term and over the long term.